Paper and cardboard as sustainable materials - Jerzy F. Latka (A+BE: Architecture and the Built Environment)
Cardboard is generally regarded as an eco-friendly or ‘green’ material. The sustainability of cardboard as a building material can be researched from different points of view, and different aspects should be taken into account. To answer the question as to whether cardboard is a ‘green’ or sustainable material for building applications, we must first define the meaning of these words. Next we need to research the various types of impact cardboard used as a building material may have on the environment.